Respuesta :
Answer:
[tex]1)(2x + y \: \: \: 2) = (1 \: \: x - y) \\ so \: compare \: 2x + y = 1...(1) \\ 2 = x - y....(2) \\ 2x + y = 1...(1) \\ x - y = 2....(2) \\ (1) + (2) \\ 3x + 0y = 3 \\ x = \frac{3}{3} = 1 ....(3)\\ \\ put \: (3)in \: (1) \\ 2 \times 1 + y = 1 \\ y = 1 - 2 \\ y = - 1 \\ here \: x = 1 \\ y = - 1 \\ 2)(x + 2y \: \: \: 3) \: and \: ( - 1 \: \: \: 2x - y) \\ here \: x + 2y = - 1...(1) \\ 2x - y = 3...(2) \\ (2) \times 2 = > 4x - 2y = 6...(3) \\ x + 2y = - 1....(1) \\ (1) + (3) \\ 5x + 0y = 5 \\ x = \frac{5}{5} = 1....(3) \\ put \: (3) \: in \: (1) \\ 1 + 2y = - 1 \\ 2y = - 2 \\ y = \frac{ - 2}{2} = - 1 \\ here \: x = 1 \\ and \: \\ y = - 1 \\ thank \: you[/tex]
Answer:
- a) (1, -1)
- b) (1, -1)
Step-by-step explanation:
a)
Compare the coordinates:
- 2x + y = 1
- x - y = 2
Add up the equations to eliminate y:
- 2x + y + x - y = 1 + 2
- 3x = 3
- x = 1
Find y:
- y = 1 - 2 = -1
b)
Compare the coordinates:
- x + 2y = -1
- 2x - y = 3
Double the second equation and add to the first one:
- x + 2y + 4x - 2y = -1 + 6
- 5x = 5
- x = 1
Find y:
- y = 2*1 - 3
- y = -1